PENGEMBANGAN DAN MODEL PENDAMPINGAN PENGGUNAAN SISTEM KEUANGAN YAYASAN: PENGEMBANGAN DAN MODEL PENDAMPINGAN PENGGUNAAN SISTEM KEUANGAN YAYASAN - Muhammad Khosyi'in; Dedy Kurniadi; Eka Nuryanto Budisusila (Universitas Negeri Surabaya, 2023)
Yayasan Pusat Kajian dan Pengembangan Islam (YPKPI) Masjid Raya Baiturrahman, Central Java is a foundation that manages several units of school institutions and mosques. Foundation finance is the field with the most complex work. The principles of transparency and accountability in financial reporting are necessary, so a system is needed that can help manage the foundation's finances correctly and according to accounting rules. The Foundation's Financial System development cannot run properly if it is not followed up with mentoring and training activities on the operation of system applications. Therefore, the Training of Trainers (ToT) for the foundation's administrative staff becomes a realistic activity to do. ToT activities are carried out with two models: scheduled and unscheduled ToT. These two methods are carried out to deal with human resource constraints (SDI) for financial administration staff who do not have an educational background or expertise in accounting/financial administration. With this ToT activity, the administrative staff of YPKPI Baiturahman Grand Mosque can manage the financial administration of the foundation and provide financial reports under accounting rules in a transparent and accountable manner